Lipidic profiling of human breast cancer plasma samples using hplc-esi-qtof (2016)
Breast cancer is an uncontrolled cell proliferation in the breast tissue causing alterations in cellular homeostasis, Including cycle regulation, redox balance, cell signaling and energy storage. As lipids are biochemical Intermediates In these processes, an untargeted lipidomic approach is proposed in order to study if there are significant differences in plasma lipid profiles between breast cancer subjects and healthy controls. In the present study, an untargeted lípidomic analysis was performed using plasma samples from a cohort consisting of 29 breast cancer subjects and 29 healthy controls. Lipids were extracted vortexing 20 æL of plasma with an MTBE/methanol/water (2:1:1,25) mixture during hour at room temperature. Subsequently, the mixture was centrifuged at 3.000Xg for 10 min at 20°C. The upper organic layer was recovered and injected onto a C8 column (Luna 3u C8 150 x 20 mm from Phenomenex) for lipid separation and further analysis by high resolution mass spectrometry (HRMS) under ESI+ and ESI- mode